Who bears the burden of debt reduction in Italy? - Hans Fehr; Anna Ruocco; Wolfgang Wiegard (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1997)
In this paper we ask who bears the burden of recent deficit reduction schemes in Italy. We implemented a reduction of the public deficit to 3 per cent of the GDP, the value that would allow Italy to meet the Maastricht Treaty criteria. The cut-down is financed by the so-called Eurotax (introduced temporarily or permanently), combined with an adjustment of the consumption tax rate or, alternatively, of lump-sum transfers, which are endogenously calculated to balance the budget. The policy reforms are simulated in a small open economy, with firms facing adjustment costs in the investment technology. The quantitative analysis is based on a numerically specified overlapping generations model of the Auerbach-Kotlikoff (AK) type. The traditional framework is extended by distinguishing between five different lifetime income classes within each age cohort. After each policy reform, we decompose the total individual welfare effects into their efficiency and redistributional components. This makes it possible to compare the implied intergenerational income effects and the efficiency effects quantitatively. Our simulations suggest that the debt reduction in Italy will increase the welfare of the future generations betwpen 1 and 2 per cent of their lifetime resources. The main reason is the implied reduction in the future net tax burdens. In order to sustain an upper deficit limit of 3 per cent of GDP permanently, an increase in consumption taxes rather than the Eurotax would be preferable.
Keywords: 330; Haushaltskonsolidierung; Steuerpolitik; Konvergenzkriterien; Generationengerechtigkeit; Italien